Water aerobics in pregnancy: cardiovascular response, labor and neonatal outcomes - Braga Angelica F; Cecatti Jose G; Pereira Rosa I; Baciuk Erica P; Cavalcante Sergio R (BMC, 2008)
Abstract Background To evaluate the association between water aerobics, maternal cardiovascular capacity during pregnancy, labor and neonatal outcomes. Methods A randomized, controlled clinical trial was carried out in which 34 pregnant women were allocated to a water aerobics group and 37 to a control group. All women were submitted to submaximal ergometric tests on a treadmill at 19, 25 and 35 weeks of pregnancy and were followed up until delivery. Oxygen consumption (VO2 max), cardiac output (CO), physical fitness, skin temperature, data on labor and delivery, and neonate outcomes were evaluated. Frequency distributions of the baseline variables of both groups were initially performed and then analysis of the outcomes was carried out. Categorical data were compared using the chi-square test, and numerical using Student's t or Mann-Whitney tests. Wilk's Lambda or Friedman's analysis of repeat measurements were applied for comparison of physical capacity, cardiovascular outcomes and maternal temperature. Results VO2 max and physical fitness were higher in both groups in the second trimester, returning to basal levels in the third trimester. In both groups, CO increased as pregnancy progressed and peak exercise temperature was higher than resting temperature, increasing further after five minutes of recovery and remaining at this level until 15 minutes after exercise completion. There was no difference between the two groups regarding duration (457.9 ± SD 249.6 vs 428.9 ± SD 203.2 minutes) or type of delivery. Labor analgesia was requested by significantly fewer women in the water aerobics group (27% vs 65%; RR = 0.42 95%CI 0.23-0.77). Neonatal results were similar in both groups. Conclusion The regular practice of moderate water aerobics by sedentary and low risk pregnant women was not detrimental to the health of the mother or the child. There was no influence on maternal cardiovascular capacity, duration of labor or type of delivery; however, there were fewer requests for analgesia during labor in the water aerobics group.